Mathematics for Life: Community Service through Realistic Mathematics Education at SMP Muhammadiyah 1 Kartasura - Santosa, Yoga Tegar; Setyaningsih, Nining; Mahmudah, Mutiara Hisda; Sukowati, Berliani Ardelia; Maulida, Dini Wardani; Wibowo, Eko Ari (Jurnal Pengabdian UNDIKMA, 2025)
This community service program aims to implement RME in secondary school mathematics, develop RME-based worksheets, assess its impact on students' outcomes, and explore teachers' and students' responses. The participants involved were students from a combined class of Grade VIII Tahfidz and Regular tracks. The activity was carried out using a Participatory Action Research model. Data were collected through questionnaires, mathematics tests, observations, interviews, and documentation. A paired sample t-test was employed to analyze the data and determine whether there was a significant difference in students’ learning outcomes prior to and following the implementation of RME. The community service results indicated that the implementation of RME successfully enhanced student engagement and understanding in mathematics learning. Statistical analysis showed a significant difference between students’ scores before and after the RME-based instruction, with the average score increasing from 46.36 to 62.44. Questionnaire responses revealed that students positively perceived the RME-based learning, particularly in terms of engagement, conceptual clarity, and meaningful learning experiences. Teachers also expressed that the RME approach provided new perspectives for delivering mathematics more contextually and engagingly, and showed interest in applying it to other mathematical topics. These findings imply that the RME approach has the potential to be sustainably integrated into broader mathematics learning through continued collaboration and material development.